Installing the Haiku Operating System on Virtual Box and Implementing File Management - Yusuf, Mohamad; Al Fatah, M Reza; Fami, Asrul; Pratama, Vemas Adi; Z, M Fauzan; Syadam, Muhammad (Journal Collabits, 2024)
This journal aims to explore the installation process of the Haiku operating system, utilizing VirtualBox and implementing effective file management techniques. Haiku, as an open-source operating system, showcases an innovative user interface and high performance. The study assesses the practicality of Haiku in virtualization through the use of the VirtualBox application. The journal presents step-by-step instructions on installing the Haiku operating system and deploying it within the VirtualBox application. Additionally, it delves into various aspects of file management in the Haiku system, including creation, deletion, and data viewing within files